The Professionalism of Islamic Religious Education Teachers in Improving The Spiritual Intelligence of Students At State Junior High School 1 Tungkal Ulu, Tungkal Ulu District, West Tanjung Jabung Regency, Jambi Province - Rosdalisa Rosdalisa; Hindun Hindun; Siti Raudatul Jannah (Dinasti Publisher, 2023)
The purpose of this study describes